PENGARUH PEMBERIAN TIMBAL (Pb) PER ORAL TERHADAP GAMBARAN HISTOPATOLOGI HEPAR Studi Eksperimental Laboratorik Pada Tikus Putih (Rattus norvegicus) Jantan Galur Wistar - Agus Suprijono; - Chodidjah; Shaher Banun (Majalah Ilmiah Sultan Agung, 2012)
Lead (Pb) is a highly toxic heavy metal which is of no use to the human body, and can accumulated in the body. The main sources of lead pollution are automobile exhaust, and contaminated food and drink. Toxic effects of lead may cause hypertension and ischemia in Heart muscle. This study aimed to investigate the effect of administration lead (Pb) orally on histopathological feature of the liver.An experimental research with a randomized control group post test design was conducted for 14 days. In this study, 25 male wistar strain rats were randomly divided into five groups to receive one of following treatment : Â standard diet and distilled water (K-I as control group), K-ll be given a standard diet, distilled water and 2,5 mg of lead (Pb)/ day per oral, K-III was given a standard diet, distilled water and 5 mg of lead (Pb)/ day per oral, K-IV was given a standard diet, distilled water and 7,5 mg of lead (Pb)/ day per oralÂ and K-IV given a standard diet, distilled water and 10 mg of lead (Pb)/ day per oral. Wet fixation methods and histopathological examination of liver were conducted after day 14. Data were analyzed with Kruskal Wallis test and continued by Mann Whitney U test to show the significancy.Results showed significanly no damage to Liver cells group I,II,III,and IV but show significantly on the fifth group.Â This study conclude that administration of lead (Pb) orally by 10 mg doses affect on the histopathological feature of the Liver of male wistar strain rats.Keywords: Lead (Pb), histopathological feature of the liver